Reflections on History from Below - Rediker, Marcus (Trashumante. Revista Americana de Historia Social, 2023)
History from below is insurgent history, deriving much of its popularity and power from movements from below. The phrase had its modern origin in the 1930s, when Lucien Febvre, Georges Lefebvre, and A.L. Morton used it to discuss the history of working people in France and England. The term exploded into wider international usage in the 1960s and 1970s as various movements arose to demand new histories. In the US and many other parts of the world the civil rights and Black power movements demanded a consideration of the past that took seriously the issues of race and slavery. Anti-war and anti-colonial movements, especially those protesting the Vietnam War, called for rethinking the histories of empire and resistance. The women’s rights movement made perhaps the greatest challenge to conventional histories, insisting that the larger part of humanity be included. All of these movements asked, who is a proper subject of history? Who is in and who is out? History from below, as a politicized type of social history, arose to answer these questions.